Separation of eutectic mixtures by a combination of fractional cryslallization and single distillation processes using open type heat pumps - G. A. Nosov; A. V. Taran; V. S. Zhiltsov (Тонкие химические технологии)
Some variants of separation of binary eutectic mixtures by combining of fractional crystallization and single distillation with using compression heat pumps open type are considered. Influence of different technological parameters on the energy efficiency are analyzed.